Professional rope access : a guide to working safely at height - McCurley, Loui, 1965- (John Wiley & Sons, Inc., 2016)
Guides the reader in the development and maintenance of a rope access program -Provides comprehensive guidance for employers, safety managers and rope access technicians to develop, maintain, and manage a rope access program -Offers specific guidance for writing a comprehensive managed fall protection plan that includes rope access -Thoroughly describes how to perform specific rope access maneuvers that can be used to offer greater safety when working at height -Shows how a well-managed rope access program can be used as a tool to get more work accomplished at a lower cost and with greater efficiency than conventional methods can achieve -Discusses and clarifies unique distinctions of equipment for rope access, as compared with equipment for fall arrest, positioning, and restraint.